A CASE REPORT OF BARDET-BIEDL SYNDROME: EMPHASIZING GENETIC COMPLEXITY AND MULTIDISCIPLINARY MANAGEMENT - Zaidi, Dua.B.; Daayl Naim Mirza,; Romesa Jamshed,; Jawed, Inshal (Journal of Ayub Medical College Abbottabad, 2025)
Bardet-Biedl Syndrome (BBS) is a rare autosomal recessive ciliopathy presenting with multisystemic manifestations. We report a case of a 17-year-old female with BBS who presented with life-threatening kidney disease. The patient exhibited classic BBS features, including retinal dystrophy, polydactyly, obesity, and cognitive impairment. Genetic analysis revealed consanguinity, underscoring the link between familial history and increased disease likelihood. This case highlights the importance of early genetic studies, comprehensive multidisciplinary care, and genetic counseling for affected families to improve patient outcomes and guide subsequent pregnancies.